ANALISIS RETAK FATIK DAN PERBAIKAN EMERGENSI DOUBLER PLATE BOTTOM KAMAR MESIN AKIBAT KAPAL KANDAS - Juan Carlos Tambunan (2022)
Ships have been a mode of transportation of goods and people since ancient times. Every ship that operates is always faced with the possibility of an accident risk (running aground). A ship that has an accident (runs aground) must be repaired immediately because it is not possible to stop because it can cause losses to several parties, therefore the ship must immediately enter the emergency dock to carry out repairs . One option for repairing a ship in an emergency is the doubler. The doubler is a method used only in emergencies because it is temporary. In this study, the author will analyze the analysis of fatigue cracking and strength from the use of the doubler found on the engine foundation of the S. Kylian tanker made of A36 steel plate material with variations in shape and loading. The method used in this research is the finite element method with the help of software structural systems. The value obtained in the analysis is the value of the von Mises stress. The results of the analysis will get the value of the von Mises stress on the square doubler plate with a loading variation of 152.5 MPa, 191.94 MPa, 231.38 MPa, and 270.82 MPa and the value of the von Mises stress doubler plate in the form of a circle with a loading variation of 152.52 MPa, 191.96 MPa, 231.41 MPa, and 270.85 MPa.